"Alienation" and critique in Marx's manuscripts of 1857–58 ("Grundrisse"). Issue 5 (3rd September 2018) - Zoubir, Zacharias
Abstract: The debate on alienation in Marx has either tended to neglect Marx's manuscripts of 1857-58 (" Grundrisse ") or has failed to provide a detailed account of that terminology in this text. This article is a philological contribution to this debate, i.e. an immanent reading of alienation in the Grundrisse with a systematic textual basis. By providing a general overview of how Marx uses terms like "alienation" ( Entfremdung ), "to alienate" ( entfremden ), "alien" ( fremd ), "alien character" ( Fremdartigkeit ) and the close yet distinct "externalisation" ( Entäuβerung ) in the Grundrisse, we set out to show precisely how the meanings and functions of this terminology can be distinguished from alienation in the so-called " Economic and Philosophical Manuscripts of 1844 " (EPM). Indeed, in the EPM, the concept of alienation refers to the inhibition of Man's generic forces by private property. There, it is thus a philosophical standpoint external to economic phenomena. In the Grundrisse, by contrast, the concept delineates three dimensions of the social and historical determination of these phenomena. First, the subordination of workers or independent producers to capital or money; second, the constitution of capital or money into independent social relations; third, the transcending character of the social reality hence produced. Nevertheless, a certain aspect of the system of alienation outlined in the EPM is taken up again in the Grundrisse: the idea that alienation calls for the integration of that which has been alienated (the productive forces) into the alienated subject (the producers).